2022
DOI: 10.1371/journal.pcbi.1010121
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of SARS-CoV-2 nucleocapsid protein induced by RNA binding

Abstract: The nucleocapsid (N) protein of the SARS-CoV-2 virus, the causal agent of COVID-19, is a multifunction phosphoprotein that plays critical roles in the virus life cycle, including transcription and packaging of the viral RNA. To play such diverse roles, the N protein has two globular RNA-binding modules, the N- (NTD) and C-terminal (CTD) domains, which are connected by an intrinsically disordered region. Despite the wealth of structural data available for the isolated NTD and CTD, how these domains are arranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 91 publications
(142 reference statements)
6
25
0
Order By: Relevance
“…In addition, we show that CA inhibited SARS-CoV-2 replication in human lung cells, further suggesting that it may influence N protein-mediated RNA packing in vivo. The latter observation is in line with recently reported models of N protein binding RNA 33 , our 1 H 15 N-HSQC NMR experiments and the N protein crystal structure binding CA, suggesting an allosteric path for N protein RNA binding inhibition by CA. Taken together, our data provide the first evidence of pharmacologically targeting the SARS-CoV-2 N protein with small molecules, thus paving the way for the rational design of new N protein modulators.…”
Section: Introductionsupporting
confidence: 92%
“…In addition, we show that CA inhibited SARS-CoV-2 replication in human lung cells, further suggesting that it may influence N protein-mediated RNA packing in vivo. The latter observation is in line with recently reported models of N protein binding RNA 33 , our 1 H 15 N-HSQC NMR experiments and the N protein crystal structure binding CA, suggesting an allosteric path for N protein RNA binding inhibition by CA. Taken together, our data provide the first evidence of pharmacologically targeting the SARS-CoV-2 N protein with small molecules, thus paving the way for the rational design of new N protein modulators.…”
Section: Introductionsupporting
confidence: 92%
“…Notably, the binding of CA to the CTD not only alters the topology but also the charge distribution of this region, which might explain why CA disrupts the N protein-RNA1 complex in solution. This hypothesis is additionally supported by a structural model of the SARS-CoV-2 N protein complexed with an RNA molecule, which we have recently reported 40 . This structural model presupposes two possibilities: one in which the CA-binding site fully overlaps with the RNA interaction site (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The CTD structure in its apo form shows an electrostatic potential distribution that is conserved amongst all N proteins from the Coronaviridae family 21,37 , with a major positively charged groove located on one side of the dimer surface (Figure 5A). This region, which is composed by Lys256, Lys257, Lys259 Lys261 and Arg262, is thought to contribute to RNA binding [38][39][40] . We observed that the positively charged groove extended towards the CA-binding pocket through Arg259, Arg276, Arg277 and Arg293 (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 evolution has been extensively studied by computational approaches [44,[57][58][59][60][61][62]. Our retrospective analysis of SARS-CoV-2 variants revealed an early divergence between conserved (ADE) and variable (neutralizing) epitopes which is based on their localization on the spike protein.…”
Section: Discussionmentioning
confidence: 94%